The Influence of Quality Assurance Institutions on Employee Performance at Nurul Jadid University - Mohammad Wali; Khoirul Umam; Hefniy Hefniy (JUMPA : Jurnal Manajemen Pendidikan, 2022)
Quality is currently a 'flagship' and becomes a competition arena in all higher education institutions and is maintained with the aim of being recognized more widely by the world of education, and quality itself becomes world competition. At this time, there are many different opinions that tend to be more towards quality competition, to be more recognized by the world, one must have a license that is recognized by the world, which seems to want that quality or (Quality) is to be made into a medium or a very accurate method. from various higher education institutions in order to compete in a very tight event. It can be seen from the current reality, there are still many higher education institutions as if they are "required" to be labeled "international quality," even though an organization must be registered beforehand in order to have an ISO (International Organization for Standardization) license. The same goes for higher education institutions. Higher education institutions, both in basic, medium educational institutions and higher education institutions, are currently competing in implementing a way to ensure the quality of a product produced can meet the highest desires of consumers, so that the provisions carried out by domestic licensed ISOs can owned. (Gumiandar, 2013)